The Effectiveness of Video Media on the Level of Knowledge, Attitudes and Practices of Covid-19 Prevention in Parents and Preschool Children - Titin Suheri (Eduvest - Journal of Universal Studies, 2022)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by the most recently discovered corona virus that can attack anyone from infants, children, to the elderly. The cause of Covid-19 transmission in preschool children is a lack of knowledge about the dangers of Covid-19 and its prevention, so that increasing knowledge and practice in preschool children is very necessary by providing education about Covid-19 prevention that can be conveyed by parents by providing various things that can improve children's knowledge, abilities, and skills through education with video media so as to increase the knowledge, attitudes, practices of parents and children.